Knowledge landscape of tumor-associated neutrophil: a bibliometric and visual analysis from 2000-2024 - Xiao, Chaoyue; Feng, Xiang; Aini, Wufuer; Zhao, Zengyi; Ding, Gouping; Gao, Yawen (Frontiers in Immunology, 2024)
Background: Neutrophils have long been consistently adjudged to hold a dominant position in acute inflammation, which once led people to undervalue their role in chronic malignancy. It is now acknowledged that neutrophils also infiltrate into the tumor microenvironment in substantial quantities and form a highly abundant immune population within the tumor, known as tumor-associated neutrophils (TANs). There has been a surge of interest in researching the eminent heterogeneity and plasticity of TANs in recent years, and scholars increasingly cotton on to the multifaceted functions of TANs so that strenuous endeavors have been devoted to enunciating their potential as therapeutic targets. Yet it remains much left to translate TAN-targeted immunotherapies into clinical practice. Therefore, there is great significance to comprehensively appraise the research status, focal point, and evolution trend of TAN by using bibliometric analysis. Methods: Publications related to TAN research from 2000 to 2024 are extracted from the Web of Science Core Collection. Bibliometric analysis and visualization were performed by tools encompassing Microsoft Excel, VOSviewer, CiteSpace, R-bibliometrix, and so on. Results: The bibliometric analysis included a total of 788 publications authored by 5291 scholars affiliated with 1000 institutions across 58 countries/regions, with relevant articles published in 324 journals. Despite China’s maximum quantity of publications and top 10 institutions, the United States is the leading country with the most high-quality publications and is also the global cooperation center. FRONTIERS IN IMMUNOLOGY published the most papers, whereas CANCER RESEARCH is the highest co-cited journal. Israeli professor Fridlender, Zvi G. is the founder, pioneer, and cultivator with the highest citation counts and H-index in the TAN area. Our analysis prefigures the future trajectories: TAN heterogeneity, neutrophil extracellular trap, the crosstalk between TANs and immunocytes, and immunotherapy will likely be the focus of future research. Conclusion: A comprehensive bibliometric and visual analysis is first performed to map the current landscape and intellectual structure of TAN, which proffers fresh perspectives for further research. The accurate identification of distinct TAN subpopulations and the precise targeting of key pro-tumor/anti-tumor subpopulations hold immense potential to develop into a TAN-targeted immunotherapy.